MENENTUKAN MINIMUM SPANNING TREE PADA JARINGAN PLN DI KECAMATAN PADANG TIMUR KOTA PADANG - Rina, Iswan; Sulistiowati, Dwi; Rianjaya, Ilham D (MAp (Mathematics and Applications) Journal, 2019)
Pada tulisan ini akan ditunjukkan penyelesaian data PLN dengan meminimumkan jarakÂ  atau menentukan jarak terpendek dari data PLN, dengan kata lain mencari minimum spanning tree dari model tree yang terbentukAbstractIn this paper we will show the completion of PLN data by minimizing distance or determining the shortest distance from PLN data, in other words looking for a minimum spanning tree from the tree model formedÂ